Transient Interdomain Interactions Modulate the Monomeric Structural Ensemble and Self‐Assembly of Huntingtin Exon 1 - Priyesh Mohanty; Tien Minh Phan; Jeetain Mittal (Advanced Science, 2025)
Abstract Polyglutamine (polyQ) tract length expansion (≥ 36 residues) within the N‐terminal exon‐1 of Huntingtin (Httex1) leads to Huntington's disease, a neurodegenerative condition marked by the presence of intranuclear Htt inclusions. Notably, the polyQ tract in Httex1 is flanked by an N‐terminal coiled‐coil domain –N17 (17 amino acids), which promotes the formation of soluble oligomers and brings the aggregation‐prone polyQ tracts in close proximity. However, the molecular mechanisms underlying the conversion of soluble oligomers into insoluble β‐rich aggregates with increasing polyQ length, remain unclear. In this study, extensive atomistic molecular dynamics (MD) simulations (aggregate time ≈0.7 milliseconds) are performed to uncover the interplay between structural transformation and domain “cross‐talk” on the conformational ensemble and oligomerization of Httex1 due to polyQ expansion. Notably, MD‐derived ensembles of N17‐Qn‐P5 monomers validated against NMR indicated that in addition to elevated α‐helicity, polyQ expansion also favored transient, interdomain (N17/polyQ) interactions which resulted in the emergence of β‐sheet conformations. Further, interdomain interactions modulated the stability of N17‐mediated polyQ dimers and promoted a heterogeneous dimerization landscape. Finally, it is observed that the intact C‐terminal proline‐rich domain (PRD) promoted condensation of Httex1 through self‐interactions involving its P10/P11 tracts while also interacting with N17 to suppress its α‐helicity.